AKUISISI BAHAN PUSTAKA DI PERPUSTAKAAN SMP N 5 KOTABARU - Nor Latifah (Jurnal Pustaka Ilmiah, 2018)
This research is entitled Acquisition of Library Material in the library of SMP N 5 Kotabaru. The purpose of the author is to find out the procedure for the acquisition of library materials that are located in the library of SMP N 5 Kotabaru. The sample of this study in the library of SMP N 5 Kotabaru. This study applies qualitative methods. How to collect data using observation, interviews and documentation. This study directs the library to require standard documents in the written acquisition library. This acquisition includes the selection of library materials carried out by teachers, staff, librarians and students. The library acquisition system is carried out through purchases, grants and contributions.